Annual Plant Reviews Online 2019
DOI: 10.1002/9781119312994.apr0628
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Pathways Important for Iron Nutrition and Biofortification of Bread Wheat

Abstract: Human iron (Fe) deficiency affects two billion people and causes a range of serious health disorders including anaemia and depressed immune function. Iron‐biofortified cereals could greatly improve food security in developing countries where dietary diversity, food fortification, and supplementation programs are limited. In this article, we present a synopsis of human Fe deficiency and highlight gross national income and anaemia prevalence around the globe in conjunction with wheat and rice production and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…Identification of the TaIRO3 , TaHRZ1 , and TaHRZ2 genes in bread wheat was performed following the guidelines outline in Bonneau et al [ 27 ]. Briefly, the OsIRO3 (LOC_Os03g26210), OsHRZ1 (LOC_Os01g49470), and OsHRZ2 (LOC_Os05g47780) DNA and protein sequences were used as queries in BLAST searches against the International Wheat Genome Sequencing Consortium (IWGSC) bread wheat reference genome databases ( (accessed on 13 April 2020), (accessed on 13 April 2020)), and subsequent putative TaIRO3 and TaHRZ sequences were validated against the rice reference genome database ( (accessed on 13 April 2020)) [ 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the TaIRO3 , TaHRZ1 , and TaHRZ2 genes in bread wheat was performed following the guidelines outline in Bonneau et al [ 27 ]. Briefly, the OsIRO3 (LOC_Os03g26210), OsHRZ1 (LOC_Os01g49470), and OsHRZ2 (LOC_Os05g47780) DNA and protein sequences were used as queries in BLAST searches against the International Wheat Genome Sequencing Consortium (IWGSC) bread wheat reference genome databases ( (accessed on 13 April 2020), (accessed on 13 April 2020)), and subsequent putative TaIRO3 and TaHRZ sequences were validated against the rice reference genome database ( (accessed on 13 April 2020)) [ 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Under Fe deficiency, wheat plants exhibit leaf chlorosis and reduced yield [ 23 ]. Recent progress in bread wheat genetics, such as the release of a fully annotated genome sequence and newly integrated databases, has allowed for efficient in silico gene identification [ 24 , 25 , 26 , 27 , 28 ]. The availability of these genetic resources has recently led to a boom in molecular characterisation efforts of wheat genes involved in Fe transport, chelation, and storage; however, there has been little characterisation of upstream regulators of Fe homeostasis to date [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the rice OsIRT1 gene (LOC_Os03g46470) has an important role in Fe uptake . The OsIRT1 promoter and/or its coding sequence were used in multi-biofortification studies in rice (Bonneau et al 2018) and three orthologous TaIRT1 genes with conserved gene structure were found in the wheat genome on chromosome group 4. It has been determined that these genes encode protein sequences with 73.0-74.2% identity with OsIRT.…”
Section: Genomic Approachesmentioning
confidence: 99%
“…Rice is the most important source of calories for humans, providing nearly half the world’s population with more than 20% of their daily caloric intake ( Bonneau et al, 2018 ). It is an important staple crop for many parts of the world, particularly in Eastern Asia, Southern Asia, and South-East Asia ( Bonneau et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is the most important source of calories for humans, providing nearly half the world’s population with more than 20% of their daily caloric intake ( Bonneau et al, 2018 ). It is an important staple crop for many parts of the world, particularly in Eastern Asia, Southern Asia, and South-East Asia ( Bonneau et al, 2018 ). Abiotic stresses, such as drought, flooding, and salinity are major limiting factors in global rice productivity ( Lafitte et al, 2004 ), therefore developing strategies to increase ascorbate concentrations in rice plants may help to mitigate the yield losses associated with these abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%